A Study of Students’ Conceptual Understanding of the Content of EVS at the Primary Stage - S. V. Sharma; Yadav, Saryug (SCHOOL SCIENCE, 2017)
A study of students’ conceptual understanding of the content of EVS has been carried out in ten primary schools in Ajmer district of Rajasthan. Research tools were administered on the students of three English medium and seven Hindi medium schools. Classroom transactions of the content of EVS taught by the teachers at primary stage were observed. Besides, teachers were interviewed to seek specific information in relation to their academic and professional qualifications as well as classroom transaction and medium of instruction. It was found from the analysis of the responses that the performance of students of English medium schools was better than that of students of Hindi medium schools. Reasons for such performance have been correlated with the lack of infrastructure in government Hindi medium schools and appropriate transactional strategies of the content of EVS.